Titanium alloy high-temperature drawing composite coating agent based on interface bonding reinforcing phase and preparation method and application thereof
Patent Information
- Application Number
- CN202511664739.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-11-13
AI Technical Summary
(1)耐温性不足:传统皮膜剂的有效工作温度通常低于800℃,在更高温度下会分解、烧结失效,失去润滑和防护作用
本发明的皮膜剂用于钛合金高温拉拔具有优异的涂层附着力:这是最核心的效果。纳米羟基磷灰石的引入,借鉴了成熟的生物界面结合原理,与钛合金表面形成强化学键合,使涂层附着力得到极大提升,达到了适用于钛合金高温拉拔的高要求。
Smart Images

Figure CN121874766B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium alloy coating agent technology, specifically relating to a high-temperature drawing composite coating agent for titanium alloys based on an interface-bonded reinforcing phase, its preparation method, and its application. Background Technology
[0002] Titanium alloys are widely used in aerospace, medical, and high-end manufacturing fields due to their high specific strength, excellent corrosion resistance, and biocompatibility. However, titanium alloys are extremely reactive at high temperatures (especially above 800°C), readily reacting with oxygen and nitrogen to form a brittle layer. Simultaneously, their high-temperature rheological stress makes them prone to sticking to the die during drawing, leading to surface scratches, a surge in drawing force, and even wire breakage, resulting in extremely low yield. Currently, hot drawing of titanium alloys mostly uses traditional calcium-based or sodium-based coating agents, or simple graphite suspensions. These traditional technologies have significant drawbacks: (1) Insufficient temperature resistance: The effective working temperature of traditional coating agents is usually below 800℃. At higher temperatures, they will decompose, sinter and fail, losing their lubricating and protective effects.
[0003] (2) Poor oxidation resistance: The solid lubricant (such as graphite) in it is rapidly oxidized in high temperature air, resulting in loss of lubrication function.
[0004] (3) Weak bonding force: The bonding force between the film layer and the titanium substrate is insufficient, and it is easy to peel off during the process of severe deformation, resulting in discontinuous lubrication.
[0005] (4) No synergistic effect: The formula is simple and each component has a single function, which cannot cope with the complex friction, oxidation and adhesion problems during high-temperature drawing of titanium alloys.
[0006] Therefore, developing a film-forming agent that can simultaneously satisfy the requirements of strong adsorption, ultra-high temperature lubrication, and excellent oxidation resistance is a key technical challenge to overcome the bottleneck in the production of high-end titanium alloy wires and tubes. Summary of the Invention
[0007] To overcome the shortcomings of existing technologies, this invention provides a high-temperature drawing composite coating agent for titanium alloys based on an interface-bonded reinforcing phase, its preparation method, and its application. This invention employs a multiphase composite system, utilizing chemical bonding, high-temperature glaze sealing, and synergistic lubrication mechanisms to solve the problems of oxidation resistance, lubrication, and adhesion in the drawing of titanium alloys at 800-1200℃, significantly improving the yield.
[0008] The technical solution adopted by this invention to solve its technical problem is: This invention provides a high-temperature drawing composite coating agent for titanium alloys based on an interface-bonded reinforcing phase, comprising, by mass percentage: Aluminum phosphate binder 15-20% Nano-hydroxyapatite 3-8% Solid lubricants 14-26% Nano-zirconia 3-4% 5-6% silicate powder Silane coupling agent 1-2% Solvent balance.
[0009] Preferably, the particle size of the nano-hydroxyapatite is 20-50 nm.
[0010] Preferably, the solid lubricant comprises graphite, hexagonal boron nitride, and nanodiamond in a mass ratio of (2.4-4.5):(2.0-4.5):1.
[0011] Preferably, the solid lubricant comprises graphite, hexagonal boron nitride and nanodiamond, in a mass ratio of (7-12):(5-10):(2-4).
[0012] More preferably, the graphite has a particle size of 1-5 μm, the hexagonal boron nitride has a particle size of 0.5-2 μm, and the nanodiamond has a particle size of 10-50 nm.
[0013] Preferably, the particle size of the nano-zirconia is 20-100 nm.
[0014] Preferably, the silicate powder is borosilicate glass powder, silicate glass powder, or alkaline earth metal silicate glass powder.
[0015] More preferably, the borosilicate glass powder has the following composition: SiO2 70-80%, B2O3 10-15%, Na2O 5-10%, and CaO 3-6%.
[0016] More preferably, the borosilicate glass powder has the following composition: SiO2 72-78%, B2O3 11-14%, Na2O 6-9%, and CaO 3-6%.
[0017] Preferably, the particle size of the silicate powder is 1-10 μm.
[0018] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane (KH-550).
[0019] Preferably, the solvent comprises deionized water and ethanol in a volume ratio of deionized water:ethanol = (6.5-7.5):(3.5-2.5).
[0020] A further preferred ratio is deionized water: ethanol = 7:3 (volume ratio).
[0021] This invention provides a method for preparing the above-mentioned titanium alloy high-temperature drawing composite coating agent based on interfacial bonding reinforcement phase, comprising the following steps: (1) Mix the aluminum phosphate binder with the solvent and stir until homogeneous; (2) Add nano-hydroxyapatite to the solution obtained in step (1) and stir for 30-40 min; (3) Add the solid lubricant to the solution obtained in step (2) and disperse it using a high-speed shear machine for 60-70 minutes at a speed of 8000-12000 rpm; (4) Add the silane coupling agent, nano-zirconia and silicate powder to the solution obtained in step (3), heat to 60-70°C and stir for 120-130 min; (5) Cool the solution obtained in step (4) to room temperature to obtain a high-temperature drawing composite film agent for titanium alloy based on interfacial bonding reinforcement phase.
[0022] This invention provides an application of the above-mentioned titanium alloy high-temperature drawing composite film agent based on the interface-bonded reinforcing phase or the titanium alloy high-temperature drawing composite film agent based on the interface-bonded reinforcing phase prepared by the above preparation method in the high-temperature drawing of titanium alloys.
[0023] Preferably, the application includes the following steps: The titanium alloy billet undergoes pretreatment, and a titanium alloy high-temperature drawing composite film agent based on the interface bonding reinforcement phase is coated on the surface of the pretreated titanium alloy billet. The billet is then preheated, cured, and drawn at high temperature. During the preheating and curing process, nano-hydroxyapatite begins to undergo an interface reaction with the titanium surface, similar to "biobonding," forming a strong transition layer.
[0024] More preferably, the pretreatment is as follows: alkaline washing (NaOH 10wt%, 80℃, 10 min) → water washing → acid washing (HF 2wt%, HNO3 10wt%, room temperature, 1 min) → water washing → drying.
[0025] More preferably, the coating is an immersion coating, and the time is 2-5 minutes.
[0026] More preferably, the preheating temperature is 150-200℃ and the time is 10-15 minutes.
[0027] More preferably, the curing temperature is 300-400℃ and the time is 20-30 minutes.
[0028] More preferably, the high-temperature drawing temperature is 800-1200℃, and the deformation is 18-40%.
[0029] The working principle of this invention, which uses an interfacially bonded reinforcing phase-based composite coating agent for high-temperature drawing of titanium alloys, is as follows: (1) Low-temperature preheating and curing stage (preheating: 150-200℃, 10-15 min; curing: 300-400℃, 20-30 min): Hydroxyapatite undergoes an interfacial bonding reaction with the titanium surface, forming a solid foundation.
[0030] Silane coupling agents promote cross-linking of components, forming a stable and dense initial film.
[0031] (2) High-temperature drawing core stage (800-1200℃): Silicate glass powder melts to form a liquid lubricating glaze, which is the core of adaptive lubrication. It can flow and fill worn areas, achieving self-repair.
[0032] The molten glass layer also acts as a physical barrier, effectively preventing oxygen from entering and protecting the internal hexagonal boron nitride and titanium matrix from oxidation.
[0033] Nano-zirconia undergoes a phase transformation at high temperatures, consuming energy, toughening the coating, and preventing the glaze from cracking due to brittleness.
[0034] Hexagonal boron nitride, protected by a glass layer, can still exist stably at the interface, providing a solid lubrication backup.
[0035] The beneficial effects of this invention are: The coating agent of this invention exhibits excellent coating adhesion for high-temperature drawing of titanium alloys: this is the most crucial effect. The introduction of nano-hydroxyapatite, drawing upon mature bio-interface bonding principles, forms a strong chemical bond with the titanium alloy surface, greatly enhancing coating adhesion and meeting the high requirements for high-temperature drawing of titanium alloys.
[0036] The coating agent of this invention exhibits excellent interfacial stability for high-temperature drawing of titanium alloys: a strong initial bond combined with the toughening and stabilizing effect of nano-ZrO2, which enables the coating to remain stable under high temperature and thermal shock, significantly extending its lifespan.
[0037] The film-forming agent of the present invention has excellent anti-oxidation and lubrication properties when used for high-temperature drawing of titanium alloys: solid lubricant and silicate glass powder achieve high lubrication and anti-oxidation properties. Attached Figure Description
[0038] Figure 1 Metallographic images of the coating agents prepared in Examples 1-3 and Comparative Examples 1-3 after high-temperature drawing of TC4 titanium alloy wire. Detailed Implementation
[0039] The present invention will be further described below with reference to embodiments.
[0040] The following will clearly and completely describe the concept, specific solutions, and technical effects of the present invention with reference to embodiments, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. The various technical features in the present invention can be combined interactively without contradicting each other.
[0041] The components, contents, and functions of the high-temperature drawing composite coating agent for titanium alloys based on interface-bonded reinforcing phase provided by this invention are shown in Table 1 below.
[0042] Table 1:
[0043] Note: The total content of the core lubrication group is 14-26%.
[0044] Example 1 A method for preparing a high-temperature drawing composite coating agent for titanium alloys based on an interface-bonded reinforcing phase, the raw material components and contents are shown in Table 2, and the method includes the following steps: (1) Drying: All solid powder components (nano hydroxyapatite, graphite, hexagonal boron nitride, nano diamond, nano zirconium oxide, silicate powder, etc.) are thoroughly dried.
[0045] (2) Preparation of base solution: Mix aluminum phosphate binder with solvent (deionized water / ethanol) and stir evenly.
[0046] (3) Biophase pre-dispersion: First, add nano-hydroxyapatite to the base liquid and stir at low speed (400 rpm) for 30 min to ensure that it is fully wetted and ready for bonding with titanium.
[0047] (4) First-stage high-speed dispersion: Add the core lubricant group (graphite, hexagonal boron nitride, nano diamond) and disperse for 60 min using a high-speed shear machine (10000 rpm).
[0048] (5) Secondary modification and dispersion: Add silane coupling agent, then add high temperature enhanced stabilizing group (nano zirconia, silicate powder), heat to 60-70°C, and stir at medium speed (700 rpm) for 120 min.
[0049] (6) Discharge: Cool to room temperature to obtain the final product.
[0050] The raw material composition of Examples 2 and 3 and Comparative Examples 1-3 is shown in Table 2, and their preparation methods are the same as those of Example 1.
[0051] Comparative Example 1: Based on Example 2, without the addition of nano-hydroxyapatite, to verify the decisive role of the interfacial bonding enhancement in relative coating adhesion.
[0052] Comparative Example 2: Based on Example 2, without adding silicate powder, this example was used to verify the core contribution of the high-temperature glaze layer to reducing pull-out force.
[0053] Comparative Example 3: Based on Example 1, graphite was replaced with an equal mass of hexagonal boron nitride, and no graphite was added, to examine the integrity of the solid lubricant combination and the lubricating effect of graphite at high temperatures.
[0054] Table 2:
[0055] The aluminum phosphate binder is designated PAS-01. The nano-hydroxyapatite has a particle size of 25-45 nm, the graphite has a particle size of 1.5-3.0 μm, the hexagonal boron nitride has a particle size of 0.8-1.5 μm, the nano-diamond has a particle size of 20-40 nm, the nano-zirconia has a particle size of 40-80 nm, the silicate powder has a particle size of 3.0-7.0 μm, and the composition is borosilicate glass powder with a composition of 74% SiO2, 12.5% B2O3, 8.5% Na2O, and 5% CaO. The silane coupling agent is KH-550, and the solvents include deionized water and ethanol in a volume ratio of 7:3.
[0056] Performance Tests and Results To verify the overall effect of the coating agent of the present invention, the coating agents prepared in Examples 1-3 and Comparative Examples 1-3 were applied to TC4 titanium alloy wire (diameter φ3.0mm) for high-temperature drawing tests.
[0057] The TC4 titanium alloy wire is first pretreated by alkaline washing (NaOH 10wt%, 80℃, 10 min) → water washing → acid washing (HF 2wt%, HNO3 10wt%, room temperature, 1 min) → water washing → drying; then dip coating is performed for 2 min.
[0058] High-temperature drawing test: The titanium alloy wire coated with the film agent was preheated and cured (preheated at 150℃ for 10 min, cured at 350℃ for 20 min), and then subjected to single-pass drawing at 850℃ (deformation amount 20%). The drawing force results of the stable drawing stage are recorded in Table 3.
[0059] Table 3:
[0060] Cross-cut adhesion test was performed on the titanium alloy billet after high temperature drawing. According to GB / T 9286-1998 standard, the coated and cured samples were tested by cross-cut adhesion test and rated from 0 (best) to 5 (worst). The cross-cut adhesion is shown in Table 4 and observed with a metallographic microscope.
[0061] See the metallographic image after dividing it into sections. Figure 1 ,from Figure 1 It can be seen that the coatings in Examples 1-3 are intact at the cross-cut test points, with only very slight or no obvious peeling; while the coating in Comparative Example 1 shows large-area peeling. This result is consistent with the cross-cut adhesion rating results in Table 4.
[0062] The surface morphology is described in Table 4.
[0063] Table 4:
[0064] Results analysis: The core role of the interfacial bonding strengthening phase (nano-hydroxyapatite): Comparing Example 2 (5%) with Comparative Example 1 (0%), the adhesion of Comparative Example 1 without nano-hydroxyapatite drops sharply to grade 4, while the pull-out force increases to 130 kgf. This proves that nano-hydroxyapatite is the key to solving the problem of strong bonding between the coating and the titanium substrate, providing a stable foundation for the entire coating system through interfacial bonding. Examples 2 (5%) and 3 (8%) both exhibited the best adhesion (grade 0), indicating that the most robust interfacial bonding can be obtained within this content range.
[0065] The decisive role of the high-temperature lubricating phase (silicate powder): Comparing Example 2 (containing 5%) and Comparative Example 2 (0%), it can be seen that Comparative Example 2, which lacks silicate powder, has the highest pull-out force (135 kgf), proving that at 850°C, the liquid glaze layer formed by the melting of silicate powder is the most important factor in reducing the pull-out force, and its adaptive lubrication mechanism is irreplaceable.
[0066] Synergistic and Irreplaceable Properties of Solid Lubricants: Comparing Example 2 and Comparative Example 3, with the same total solid lubricant content (14% in both), Comparative Example 3, which completely replaces graphite with an equal amount of hexagonal boron nitride, still exhibits a significantly higher pull-out force (138 kgf) than Example 2 (115 kgf). This indicates that graphite plays a unique and irreplaceable lubricating role at high temperatures. The composite lubrication system formed by graphite, hexagonal boron nitride, and nanodiamond is superior to single-type lubricants, providing more effective early-stage protection for high-temperature glaze lubrication.
[0067] The Importance of Formulation Balance: Example 2 employed moderate and balanced amounts of key components such as nano-hydroxyapatite (5%), silicate powder (5%), and solid lubricant, achieving optimal performance in both adhesion (grade 0) and high-temperature pull-out force (115 kgf). In contrast, Examples 1 (lower hydroxyapatite content, higher total lubricant content) and 3 (higher hydroxyapatite content, highest total lubricant content) did not achieve this optimal effect, demonstrating that simply increasing the content of a single component is not effective; the key lies in the synergy and balance of the formulation.
[0068] In summary, the composite film agent described in this invention achieves high adhesion and low pull-out force during high-temperature drawing of titanium alloys through the synergistic effect of its components. The formulation in Example 2 exhibits the best overall performance.
[0069] The above is a detailed description of the preferred embodiments of the present invention. However, the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention. All such equivalent modifications or substitutions are included within the scope defined by the claims of the present invention.
Claims
1. A high-temperature drawing composite coating agent for titanium alloys based on an interface-bonded reinforcing phase, characterized in that, Included by mass percentage: Aluminum phosphate binder 15-20% Nano-hydroxyapatite 3-8% Solid lubricant 14-26% Nano-zirconia 3-4% 5-6% silicate powder Silane coupling agent 1-2% Solvent balance; The solid lubricant comprises graphite, hexagonal boron nitride, and nanodiamond in a mass ratio of (2.4-4.5):(2.0-4.5):
1.
2. The titanium alloy high-temperature drawing composite film agent based on interface-bonded reinforcing phase according to claim 1, characterized in that, The nano-hydroxyapatite has a particle size of 20-50 nm.
3. The titanium alloy high-temperature drawing composite film agent based on interface-bonded reinforcing phase according to claim 1, characterized in that, The graphite has a particle size of 1-5 μm, the hexagonal boron nitride has a particle size of 0.5-2 μm, and the nanodiamond has a particle size of 10-50 nm.
4. The high-temperature drawing composite coating agent for titanium alloys based on interface-bonded reinforcing phase according to claim 1, characterized in that, The particle size of the nano-zirconia is 20-100 nm; The silicate powder is borosilicate glass powder, silicate glass powder, or alkaline earth metal silicate glass powder. The particle size of the silicate powder is 1-10 μm.
5. The titanium alloy high-temperature drawing composite film agent based on interface-bonded reinforcing phase according to claim 4, characterized in that, The borosilicate glass powder has the following composition: SiO2 70-80%, B2O3 10-15%, Na2O 5-10%, and CaO 3-6%.
6. The titanium alloy high-temperature drawing composite film agent based on interface-bonded reinforcing phase according to claim 1, characterized in that, The silane coupling agent is γ-aminopropyltriethoxysilane; The solvent includes deionized water and ethanol, with a volume ratio of deionized water:ethanol = (6.5-7.5):(3.5-2.5).
7. The method for preparing the high-temperature drawing composite coating agent for titanium alloys based on interfacially bonded reinforcing phases according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix the aluminum phosphate binder with the solvent and stir until homogeneous; (2) Add nano-hydroxyapatite to the solution obtained in step (1) and stir for 30-40 min; (3) Add the solid lubricant to the solution obtained in step (2) and disperse it using a high-speed shear machine for 60-70 minutes at a speed of 8000-12000 rpm; (4) Add the silane coupling agent, nano-zirconia and silicate powder to the solution obtained in step (3), heat to 60-70°C and stir for 120-130 min; (5) Cool the solution obtained in step (4) to room temperature to obtain a high-temperature drawing composite film agent for titanium alloy based on interfacial bonding reinforcement phase.
8. The application of the titanium alloy high-temperature drawing composite coating agent based on the interface-bonded reinforcing phase according to any one of claims 1-6 or the titanium alloy high-temperature drawing composite coating agent based on the interface-bonded reinforcing phase prepared by the preparation method according to claim 7 in the high-temperature drawing of titanium alloys.
9. The application according to claim 8, characterized in that, The application includes the following steps: The titanium alloy billet is pretreated by coating the surface of the pretreated titanium alloy billet with a titanium alloy high-temperature drawing composite film agent based on the interface bonding reinforcement phase, preheating, curing, and high-temperature drawing.
10. The application according to claim 9, characterized in that, The pretreatment process is: alkaline washing → water washing → acid washing → water washing → drying. The coating is an immersion coating, and the time is 2-5 minutes; The preheating temperature is 150-200℃, and the time is 10-15 minutes; The curing temperature is 300-400℃, and the time is 20-30 minutes; The high-temperature drawing temperature is 800-1200℃, and the deformation is 18-40%.
Citation Information
Patent Citations
Multi-particle synergistic water-soluble titanium alloy hot rolling lubricant and preparation method thereof
CN110776987A
High-temperature solid lubricant for titanium alloy extrusion and preparation method thereof
CN115386410A